Altering Physical Activity Influences Insulin Responses to Glucose Ingestion in Healthy Adults - Timmerman, Kyle L.; Ballard, Kevin D.; Volk, Gabrielle A.; Deal, Michael A.; Meisler, Adam J.; Karrow, Jenna M.; Good, Alex P.; Reynolds, Sandy T. (International Journal of Sports Medicine, 2018)
This study determined if varying physical activity (PA) the day prior to an oral glucose tolerance test (OGTT) differentially influenced postprandial glucose and insulin kinetics. Fifteen healthy, young adults participated in three OGTT trials the morning after performing 50% (LOW), 100% (HABITUAL), or 150% (HIGH) of their habitual PA (determined by 7-day pedometry). Trials were randomized and separated by at least 1-wk. For each OGTT trial, blood glucose and insulin were measured after an overnight fast and at 30-min intervals for 2 h following ingestion of the glucose beverage. Between-trial differences were analyzed using a general linear model with repeated measures. Subjects successfully achieved the desired percentage of habitual steps prior to each trial: LOW: 51±5%, HABITUAL: 99±6%, and HIGH: 149±9%. Fasting blood glucose and glucose total area under the curve (AUC) did not differ between trials. Serum insulin AUC was lower (p<0.05) following the HIGH (34,158±8,786 pmol·min·L−1) compared to the LOW (40,738±9,276 pmol·min·L−1) trial. No differences were observed when the LOW and HIGH trials were compared to HABITUAL. These data suggest that varying the PA level (from 50 to 150% of habitual PA) the day prior to an OGTT influences the insulin (but not blood glucose) response to an OGTT.
Keywords: insulin sensitivity; sedentary behavior; pedometry; accelerometry; metabolic health